Efeito de diferentes estratégias para adesão de um adesivo universal no modo autocondicionante: ensaio clínico, randomizado, duplo cego - Scheffer , Rafael Ferreira (2018)
This double-blind randomized clinical trial evaluates strategies for improving the bonding of universal adhesive to enamel in non-carious cervical lesions (NCCL). Methods: 260 restorations were randomly placed in 50 patients according to the following groups: SE – Self-etch; SEE - Selective etching; SE2X - Self-etch doble time; SE1+ - Self-etch additional layer. The restorations were evaluated after one week (baseline) 6 months, using the FDI and USPHS criteria. Statistical analyses were performed using Friedman and McNemar test (=0.05). Results: Thiteen restorations were lost at 6 months (5 for SE, 1 for SEE, 4 for SE2X and 3 for SE1+) (p > 0.05 between groups). Post-operative sensitivity wasn’t observed in any of the recall periods. fifty-six restorations were considered to have minor discrepancies in marginal adaptation at the 6-month recall using the FDI criteria (16 for SE, 08 for SEE, 16 for SE2X and 16 for SE1+; p > 0.05 between groups). Eleven restorations were considered to have minor discrepancies in marginal discoloration at the 6-month recall (04for SE, 01 for SEE, 03 for SE2X and 03 for SE1+; p > 0.05 between groups). Conclusion: The different strategies application of universal adhesive showed similar clinical behavior of composite restorations placed in NCCLs over 6 months.